2016
DOI: 10.1155/2016/5493279
|View full text |Cite
|
Sign up to set email alerts
|

YiQiFuMai Powder Injection Ameliorates Cerebral Ischemia by Inhibiting Endoplasmic Reticulum Stress‐Mediated Neuronal Apoptosis

Abstract: YiQiFuMai (YQFM) powder injection as a modern preparation derived from Sheng Mai San, a traditional Chinese medicine, has been widely used in the treatment of cardiovascular and cerebrovascular diseases. However, its neuroprotective effect and underlying mechanism in cerebral ischemia remain to be explored. The present study was designed to investigate the neuroprotective effect of YQFM on endoplasmic reticulum (ER) stress-mediated neuronal apoptosis in the permanent middle cerebral artery occlusion- (MCAO-) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Aberrant mitochondrial dynamics play critical roles in the pathological processes of ischemic stroke [ 14 ]. Previous studies have shown that YQFM protects against myocardial ischemia/reperfusion injury via AMPK pathway mediated mitochondrial fission [ 39 ] and oxygen-glucose deprivation-induced PC12 cell apoptosis through ER stress [ 36 ]. However, the effects of YQFM against mitochondrial dysfunction and excessive fission induced by ischemic stroke have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant mitochondrial dynamics play critical roles in the pathological processes of ischemic stroke [ 14 ]. Previous studies have shown that YQFM protects against myocardial ischemia/reperfusion injury via AMPK pathway mediated mitochondrial fission [ 39 ] and oxygen-glucose deprivation-induced PC12 cell apoptosis through ER stress [ 36 ]. However, the effects of YQFM against mitochondrial dysfunction and excessive fission induced by ischemic stroke have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Rg1 prevents myocardial hypoxia/reoxygenation injury by regulating mitochondrial dynamics imbalance [ 35 ]. Recent studies have also indicated that YQFM protects against ischemic injury through regulating endoplasmic reticulum stress-mediated neuronal damage [ 36 ]. YQFM also ameliorates blood-brain barrier (BBB) dysfunction through NF- κ B and ROCK1/MLC signaling pathways [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting analysis was performed as reported previously [ 54 ]. In brief, the brain tissues or cells were lysed and centrifuged at 12,000× g for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…As a prescription commonly used in Tibetan medicine to treat ischemic sequelae, our research group proved that the anti-cerebral ischemia effect of ErShiWei ChenXiang pills may be related to its regulation of Bcl-2 family, inhibition of apoptosis, and increase of energy supply (Hou et al, 2020). While regulating Bcl-2 family members, AnNao tablets (Zhang et al, 2020) and YiQi FuMai powder injection (Cao et al, 2016; may also be involved in inflammation and mitochondrial autophagy to maintain mitochondrial MMP and energy production. In addition, both TongXinLuo's regulation of AKT/ERK signaling (Yu et al, 2016;Cheng et al, 2017) and XingNaoJing injection's regulation of the PI3K-AKT pathway ultimately contributed to the regulation of Bcl-2 and the inhibition of ischemic neuron apoptosis.…”
Section: Authorized Products For Stroke Improvement By Regulating Mitmentioning
confidence: 87%